44. NURSING IN ETHNIC MINORITY COMMUNITIES: AN EXPLORATORY QUALITATIVE STUDY ON CHILD MARRIAGE (Vietnam Journal of Community Medicine, 2025)
Objectives: Child marriage reflects gender inequality and poor access to adolescent reproductive health in ethnic communities. This study explored perceptions of child marriage and the role of nurses in community-based prevention.Methods: An explorative qualitative study was conducted in Moc Chau with 21 participants. Using Braun & Clarke’s framework.Results: The study results showed that child marriage is normalized among Hmong people. Barriers include limited knowledge, language, and communication taboos.Conclusion: Nurses are well-positioned to intervene but require better support. Strengthening nursing capacity and intersectoral collaboration is essential for effective prevention.
Keywords: Early marriage; Ethnic minorities; Adolescent reproductive health; Community nursing; Health education and communication.